Diseño de un mortero con arena de río de la Provincia de Pastaza, utilizando Cemento Portland tipo i y he incluido flujo piroclástico para el uso de impresoras 3d - Vallejo Amaguaya, Karina Mabel (2021)
The boom of 3D printing, a novel technology that allows considerable savings, is used in construction, where printing requires materials with specific characteristics, equipment and procedures that provide its use in this industry. Ecuador does not apply this technology completely; the greatest difficulty is directly involved in the need for a local material that allows the design of mortars with the appropriate characteristics to adapt to this equipment. The aim of this study was to develop mortars with river sand from the province of Pastaza, portland cement type I and HE with the addition of pyroclastic flow, for its application in 3D printers. Therefore, eight mortar mixtures were prepared with different dosages using two types of dry aggregate, cement and pyroclastic flow. Both the aggregate and the designed mortars were subjected to laboratory tests to check their characteristics with the respective standards, as well as their comparison with previous studies and printing on the 3D printer prototype. The results showed that the mortars designed with the studied aggregate plus portland cement type HE without pyroclastic flow, presented better characteristics both in mortar design and 3D printing. The design of these mortars will be useful for 3D printing reaching high compressive strengths, reducing the setting time and presenting good workability, flowability, extrudability and printing quality, suggests performing tests on a real scale to optimize the printable mortars